Selenate and selenite on yield and agronomic biofortification with selenium in rice - Boldrin, Paulo Fernandes (2012)
The objective of this work was to evaluate the effect of doses of selenate and selenite on biofortification with Se, as well the influence of these forms of Se in the levels of P, S, Fe, and Zn in grains of rice (Oryza sativa). The experiment was conducted in a greenhouse, in pots with 4 dm3 of a sandy clay loam Latosol, with medium texture, in a 5x2 factorial arrangement with five doses of Se (0, 0.75, 1.50, 3.0, and 6.0 mg dm-3) and two forms of Se (selenate and selenite). Selenate provided greater efficiency of root uptake of Se, plant‑use efficiency, translocation from roots to shoots, and content of this element in rice grains. The application of Se during fertilization influences the levels of P, S, and Zn, but does not affect those of Fe in rice grains.